80 The impact of sex and physical performance on long-term mortality in older patients with myocardial infarction. (8th December 2021) - Tonet, Elisabetta; Ariza-solé, Albert; Serenelli, Matteo; Formiga, Francesc; Juan, Sanchis; Pavasini, Rita; Diez-villanueva, Pablo; Vitali, Francesco; Bonanad, Clara; Grazzi, Giovanni; Carol, Antoni; Chiaranda, Giorgio; et al.
Abstract: Aims: To investigate the prognostic role of sex and physical performance on long-term mortality in older adults hospitalized for acute coronary syndrome (ACS). Methods and results: The analysis is based on older (≥70 years) ACS patients included in the FRASER, HULK, and LONGEVO SCA prospective studies. Physical performance was assessed with the Short Physical Performance Battery (SPPB). The primary outcome was all-cause mortality. The study included 1388 patients, 441 (32%) were women. At presentation, women were older and more compromised than men. After a median follow-up of 998 (730–1168) days, all-cause death occurred in 334 (24.1%) patients. At univariate analysis, female sex was related to increased risk of death. After adjustments for confounding factors, female sex was no longer associated with mortality. Women showed poor physical performance compared with men ( P < 0.001). SPPB values emerged as independent predictor of death. Including clinical features and SPPB in the multivariable model, we observed a paradigm shift in the prognostic role of female sex that becomes a protective factor (HR: 0.73, 95% CI: 0.56–0.96). Sex and physical performance showed a significant interaction ( P = 0.03). For lower SPPB values (poor physical performance), sex-related changes in mortality were not recorded, while in patients with higher SPPB values (preserved physical performance), female sex was associated with better survival. Conclusions: Two key findings emerged from the present real-life cohort of older ACS patients: (i) physical performance strongly influences long-term mortality and (ii) women with preserved physical performance have a better outcome compared to men.